Engineering Extracellular Matrix Proteins to Enhance Cardiac Regeneration After Myocardial Infarction - Esmaeili, Hamid; Li, Chaoyang; Fu, Xing; Jung, Jangwook P. (Frontiers in Bioengineering and Biotechnology, 2021)
Engineering microenvironments for accelerated myocardial repair is a challenging goal. Cell therapy has evolved over a few decades to engraft therapeutic cells to replenish lost cardiomyocytes in the left ventricle. However, compelling evidence supports that tailoring specific signals to endogenous cells rather than the direct integration of therapeutic cells could be an attractive strategy for better clinical outcomes. Of many possible routes to instruct endogenous cells, we reviewed recent cases that extracellular matrix (ECM) proteins contribute to enhanced cardiomyocyte proliferation from neonates to adults. In addition, the presence of ECM proteins exerts biophysical regulation in tissue, leading to the control of microenvironments and adaptation for enhanced cardiomyocyte proliferation. Finally, we also summarized recent clinical trials exclusively using ECM proteins, further supporting the notion that engineering ECM proteins would be a critical strategy to enhance myocardial repair without taking any risks or complications of applying therapeutic cardiac cells.